Ferromagnetic Resonance Theory and Applications - Yalcin, Orhan (IntechOpen, 2013)
The book Ferromagnetic Resonance - Theory and Applications highlights recent advances at the interface between the science and technology of nanostructures (bilayer-multilayers, nanowires, spinel type nanoparticles, photonic crystal, etc.). The electromagnetic resonance techniques have become a central field of modern scientific and technical activity. The modern technical applications of ferromagnetic resonance are in spintronics, electronics, space navigation, remote-control equipment, radio engineering, electronic computers, maritime, electrical engineering, instrument-making and geophysical methods of prospecting.